Efforts to Surpass Converse and Adidas (aSSIST Business Review, 2025)
This study analyzes Nike's success strategy in surpassing Converse and Adidas, the dominant players in the basketball shoe market of the 1980s, through the perspectives of the SER-M model (Subject-Environment-Resource) and the Weight-Order model. Nike effectively utilized its limited resources by adopting a focus-and-concentrate strategy centered on the rookie athlete Michael Jordan, combined with storytelling and limited-edition marketing. This strategy optimized the allocation and sequencing of resources, leading to the successful branding of Air Jordan. More than just basketball shoes, Air Jordan became a cultural icon, recording sales of $130 million in its first year and continuing to grow, capturing 86% of the basketball shoe market share by 2021. Nike's success demonstrates how leadership, environmental opportunity, and strategic resource allocation within the SER-M model interact to achieve results. The Weight-Order model contributed to optimal outcomes by facilitating efficient resource allocation and execution sequencing, even under constraints. This study highlights the importance of the SER-M model and the Weight-Order model in corporate strategy development, emphasizing how limited resources and differentiated marketing can maximize business performance.
Keywords: Nike; Air Jordan; SER-M model; Weight-Order model; marketing strategy; focus-and-concentrate; brand innovation